Balto-Finnic Personal Name Suffixes - Joalaid, Marje (York University, 2009)
The Balto-Finnic peoples have always formed their personal names using primarily personal name suffixes. After Christianizing, these peoples as most other European peoples have had Christian names: the Orthodox (Greek-Catholic) people (Karelians, Vepsians, Votes and Ingrians or Izhorians) mostly names of Greek origin, the Roman-Catholics (from the 16th century the Lutherans) (Finns, Estonians, Livonians) names of Latin origin. The Balto-Finnic name suffixes occur in the hypocoristic modifications of the Christian names. The most popular and with great probability also the oldest Balto-Finnic name suffix is -'oi' ('-ęi'). According to old documents it occurs already in the pre-Christian names. The old Balto-Finnic place name with the suffix '-la' also consists of a personal name with the suffix '-oi' before the place name suffix '-la'. The suffix '-oi' is originally a diminutive suffix, although it has lost its diminutive character in names. In different Balto-Finnic languages it has preserved its primary phonetic form (in Finnish, Karelian and Ingrian) or it developed phonetically (Votic -'oi' > '-o', Estonian '-oi' > '-o' > '-u'). In addition to '-oi' there are some other personal name suffixes which occur in different Balto-Finnic languages: '-u', the plosive '+ s' ('-ts', '-ks', '-ps') '-ne(n)', '-uk(ka)' / '-kas', '-k(k)i', and others.